From rivers to natural gas: The influence of allochthonous inputs on marine nitrogen fixation and the carbon cycle - Weber, Sarah C. (Georgia Institute of Technology, 2016)
The Western Tropical North Atlantic (WTNA) was once thought to be a net source of carbon dioxide (CO₂) to the atmosphere, but recent studies have shown that this Amazon River influenced region may actually act as a net sink for CO₂. During a 2010 research cruise to the WTNA, we characterized the impact of the Amazon River on offshore diazotrophy (N₂-fixation) and the resulting stimulation of biological carbon export from surface waters. Through the delivery of phosphate- and silicate-replete waters to the nitrogen (N) limited surface waters of the WTNA, the aging Amazon River plume promotes the growth of diatom-diazotoph associations (DDAs). Regions supporting large DDA blooms were associated with increased pCO₂ and DIC drawdown in the surface waters, reflecting the net export of carbon from the mixed layer. The existence of this biologically mediated linkage between the C and N cycles in productive surface waters is well known, but we have only recently discovered a stimulatory relationship in deep waters between oil/gas release and N₂-fixation. This association was first observed after the Deepwater Horizon oil spill in 2010 and we again saw evidence for it in the days following the Hercules 265 natural gas blowout. This blowout event was characterized by the release of an unknown quantity of natural gas into the shelf waters of the Northern Gulf of Mexico, but we detected a response from the marine microbial community within days. We observed a significant drawdown of dissolved oxygen and found biogeochemical evidence for the incorporation of methane-carbon into the food web, along with a modest stimulation of N₂-fixation. The episodic nature of anthropogenic blowouts makes them difficult to study, so we use cold seeps in the Gulf of Mexico as natural analogues. Interestingly, we have measured both methane oxidation and N₂-fixation at depth above some of the more active seeps. Using NanoSIMS analyses, we have taken the first steps towards physically characterizing the organisms utilizing these metabolisms. It appears that different organisms are carrying out these processes, with CH₄-assimilation occurring primarily in individual particles or small aggregates, whereas N₂-fixtion was associated with larger, sulfur-containing aggregates. Continued NanoSIMS work in combination with the use of microbial ID techniques will help to further characterize these unique deepwater diazotrophs. M.S.